Analisis Korelasi Hasil Pengujian Unconfined Compressive Strength (UCS) & Point Load Index (PLI) Batuan pada Formasi Kampungbaru, Kabupaten Kutai Kartanegara - Akbar Nazaruddin; Albertus Juvensius Pontus; Agus Winarno; Tommy Trides; Lucia Litha Respati (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2026)
Slope stability studies are crucial in determining the sustainability and operational safety of mining activities. This research was conducted to analyze the correlation between rock porosity and Unconfined Compressive Strength (UCS) results, as well as the corrleations between Point Load Index (PLI) and Unconfoned Compressive Strength (UCS) results. These two correlations form the primary components of the study. Three types of rock were tested claystone, coal, and siltstone. The results of the study are as follows for the correlation between porosity and Unconfoned Compressive Strength (UCS), claystone yielded a coefficient of determination (R2) of 0.32 is classified as weak correlation, with the linear regression equation Y=-0.11X+6.98. Coal yielded an (R2) of 0.56 is classified a moderate correlation, with the equation Y=-1.98X+103.77. Siltstone yielded an (R2) of 0.86 is classified a strong correlation, with the equation Y=-0.38X+20.02. Regarding the correlation between Point Load Index (PLI) and Unconfoned Compressive Strength (UCS), claystone achieved an (R2) of 0.12 is classified a very weak correlation, with the linear regression equation Y=8.91X. Coal achieved an (R2) of -0.27 is classified a very weak correlation, with the equation Y=27.87X. Lastly, siltstone achieved an (R2) of -0.45 is classified a very weak correlation, with the linear regression equation Y=24,90X.